ANALISIS PEMASANGAN BOX CULVERT (2 m x 1.5 m) SEBAGAI SALURAN PENYEIMBANG DI KM 54+490 SAMPAI DENGAN KM 55+070 - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Felix Joel Ledowikj (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
Train is one of the land transportation infrastructure that have an important role in distributing things and passengers. However, currently there are still some obstacles in the operation of the railway, mainly caused by natural disasters. In general, the National DisasterManagement Agency (BNPB) noted that 95% of disasters that occurred in Indonesia were dominated by hydrometeorological disasters, one of which was flooding.In February 2021, there was a flood on the railway line, precisely between Lemahabang -Kedunggedeh Station, DAOP 1 Jakarta on the rail line KM54+490 to KM 55+070 which caused the body of the upstream and downstream rail lines collapse, resulting in the cessation of the train operations.Therefore, a total of 31 box culverts will be planned to drain the 5-year flood discharge and become a balancing channel for the railroad if the flood phenomenon occurs again